Educação, globalizações e cosmopolitismos: novos direitos, novas desigualdades - Carlos Vilar Estêvão (Universidade do Minho, 2009)
Considering the actual context where new inequalities and new injustices emerge, I aim to articulate the process of globalisation with the construction of cosmopolitanism and social justice as I distinguish in this discussion various types of cosmopolitanism such as the neoliberal and democratic types. Within the latter, I deepen the notion of cosmopoliticity in order to stress the idea of universality as well as global dialogicity and politicity. The end of this essay explains how democratic cosmopoliticity influences education and educational administration so that it contributes to a stronger global justice and the "cultivating humanity".